The protective role of exogenous Ghrelin versus its combination with Zingerone on experimentally induced gastric ischemic-reperfusion in adult male albino rats: The protective role of exogenous Ghrelin - Samar Mohamed Reda,; Heba M. Abdel-Aziz,; Samy, Walaa; Abeer A. Abdelrahman,; Noura H. Mekawy, (Cellular and Molecular Biology, 2022)
Ghrelin is a gut hormone has stimulatory properties on food intake, fat deposition and growth hormone release. Zingerone is a component of ginger with multiple pharmacological activities. They were established that have protective roles against oxidative stress actions. We planned this study to evaluate pretreatment exogenous Ghrelin alone and or accompanied with Zingerone on ischemia-reperfusion injury to gastric fundus wall. Fifty male albino rats were used and subdivided into control, ischemic- reperfusion, Ghrelin pretreated and Ghrelin Zingerone pretreated groups. Specimens from the stomach fundus were processed for histological, immunohistochemical study and gene expression using real time PCR. Morphometric and statistical analyses were also carried out in this research. In ischemic-reperfusion sections, there were deep erosion and distortion of the mucosa. Chief cells appeared with vacuolated cytoplasm and pyknotic nuclei. Congestion of blood vessels with extravasation and cellular infiltration was also noticed. There was a decrease in mucous secreted cells in PAS-stained sections. Sections from Ghrelin pretreated and Ghrelin Zingerone pretreated groups showed a great improvement. In addition, gastric tissues with the ischemia-reperfusion group showed a significant decrease in enos and nrf2 mRNA expression while there was a significant increase in HIF and VEGF, which is counteracted to Ghrelin pretreated and Ghrelin Zingerone pretreated groups. This study revealed the vital protective role of Ghrelin in concomitant with Zingerone than pretreated Ghrelin alone on attenuating the damage changes of fundus that occurred after experimentally induced gastric ischemia-reperfusion.